Mineral content of foodstuffs osmium in foodstuffs - Szabó S. András (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2020)
This paper – as a part of a series of articles about minerals after the former article about palladium - deals with topics of toxic trace elements. In the paper information is given about a new microelement (osmium), belonging to the platinum group metals.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék